Legal Protection for the Welfare of the Generation Z Exodus: A Constitutional Law Perspective in Fulfilling Constitutional Rights - Nugraha, Tirta; Guntara, Deny; Rahmatiar, Yuniar; Fauziah, Margie Rahayu (IHSA Institute, 2025)
This study aims to examine legal protection for the welfare of Generation Z in the context of exodus or migration, both abroad and between regions, triggered by dissatisfaction with socio-economic conditions at home. From the perspective of constitutional law, Generation Z as part of Indonesian citizens has constitutional rights to work, education, and social welfare as guaranteed in Article 27 paragraph (2), Article 28C, Article 28D paragraph (1), and Article 28H paragraph (1) of the 1945 Constitution of the Republic of Indonesia. This study uses a qualitative method with a normative legal approach and descriptive-analytical specifications, with data collection techniques through literature studies of national laws and international legal instruments. The results of the study show that although the basic rights of Generation Z have been guaranteed in various laws, their implementation is still weak. High unemployment, unequal access to education and health, and minimal protection of the informal sector such as the gig economy, have encouraged the emergence of the Gen Z migration phenomenon, including through the hashtag